2006
DOI: 10.1152/ajpcell.00028.2005
|View full text |Cite
|
Sign up to set email alerts
|

Acute hypoxia selectively inhibits KCNA5 channels in pulmonary artery smooth muscle cells

Abstract: Acute hypoxia causes pulmonary vasoconstriction in part by inhibiting voltage-gated K(+) (Kv) channel activity in pulmonary artery smooth muscle cells (PASMC). The hypoxia-mediated decrease in Kv currents [I(K(V))] is selective to PASMC; hypoxia has little effect on I(K(V)) in mesenteric artery smooth muscle cells (MASMC). Functional Kv channels are homo- and/or heterotetramers of pore-forming alpha-subunits and regulatory beta-subunits. KCNA5 is a Kv channel alpha-subunit that forms functional Kv channels in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
60
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 65 publications
(62 citation statements)
references
References 59 publications
2
60
0
Order By: Relevance
“…Inhibition of K ϩ channels causes membrane depolarization, increases open probability of VDCC, promotes Ca 2ϩ influx, increases [Ca 2ϩ ] cyt , and triggers PASMC contraction. Our group and others have demonstrated that chronic hypoxia results in decreased expression and function of K v channels (11,39,41,42,53,54,61,62,65). In the present study, we show that, in addition to inhibiting K v channels, chronic hypoxia selectively enhances VDCC function and expression in PA and PASMC (but not in MA).…”
Section: Discussionsupporting
confidence: 67%
“…Inhibition of K ϩ channels causes membrane depolarization, increases open probability of VDCC, promotes Ca 2ϩ influx, increases [Ca 2ϩ ] cyt , and triggers PASMC contraction. Our group and others have demonstrated that chronic hypoxia results in decreased expression and function of K v channels (11,39,41,42,53,54,61,62,65). In the present study, we show that, in addition to inhibiting K v channels, chronic hypoxia selectively enhances VDCC function and expression in PA and PASMC (but not in MA).…”
Section: Discussionsupporting
confidence: 67%
“…Some studies suggested a prominent role for the K V 1.5 subunit (8, 73); however, this was countered by data from non-PASMC expression systems indicating that expression of either K V 1.5 or K V 1.2 resulted in currents that were insensitive to hypoxia (160,176) or only inhibited at very high E m (103). Interestingly, a hypoxiasensitive I K did develop when K V 1.2 and K V 1.5 were coexpressed (103, 160) or when K V 1.5 was expressed in PASMCs (176). These findings suggest that O 2 sensitivity may be determined by the host cell (41, 133).…”
Section: Circulatory Systemmentioning
confidence: 99%
“…4b) allows for the conclusions that: 1) either inhibition of respiration is not the single mechanism underlying HPV; 2) that the difference in responses of PASMC and ASMC to hypoxia is caused by mechanisms downstream of a reduction in respiration, e.g. by different ion channel expression [31], or specific regulation of ion channel function [32]; or 3) with regard to ASMC, ASMC react similar to PASMC as they face rather high PO 2 in vivo with the aorta carrying well oxygenated blood. The latter explanation is supported by the fact that, in contrast to ASMC, RASMC showed no hypoxia-induced membrane hyperpolarisation, which corresponds to higher respiration in hypoxia.…”
Section: Pulmonary Circulation N Sommer Et Almentioning
confidence: 99%